2022
DOI: 10.2991/assehr.k.220203.013
|View full text |Cite
|
Sign up to set email alerts
|

Millennial’s Organizational Citizenship Behavior (OCB)

Abstract: Research on Organizational Citizenship Behavior (OCB) was carried out more than three decades ago. In 2025, the millennial generation will dominate the workforce, which has different characteristics from the previous generation. This literature review aims to map out research on OCB in the millennial generation in Indonesia, based on samples, objectives, determinant factors, and results of OCB in the millennial generation in Indonesia. This study uses the PRISMA method and uses data obtained from the Garuda po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…A variety of internal and external factors influence organizational citizenship behavior. Sofiah et al (2022) found that external factors positively impact organizational citizenship behavior, including leader-member exchange, employee engagement, organizational culture, perceived organizational support, job satisfaction, work-life balance, transactional leadership, transformational leadership, clan culture, affective commitment, and need of affiliation. In addition, Madiistriyatno & Hadiwijaya, (2020) also stated that external factors, including management systems, leadership systems, and company culture, impact OCB.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A variety of internal and external factors influence organizational citizenship behavior. Sofiah et al (2022) found that external factors positively impact organizational citizenship behavior, including leader-member exchange, employee engagement, organizational culture, perceived organizational support, job satisfaction, work-life balance, transactional leadership, transformational leadership, clan culture, affective commitment, and need of affiliation. In addition, Madiistriyatno & Hadiwijaya, (2020) also stated that external factors, including management systems, leadership systems, and company culture, impact OCB.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, decreasing OCB will have negative consequences such as diminished firm reputation, increased interpersonal conflicts, and reduced organizational efficiency (Fatima et al, 2015). The organization's development will be hindered if individuals solely focus on fulfilling their formal responsibilities without making additional contributions beyond their assigned tasks (Sofiah et al, 2022). Hence, recognizing the significance of OCB for companies, it is necessary to foster OCB among millennial employees.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Job satisfaction from millennial workers has a positive impact on individual performance (Waworuntu et al, 2022). Millennial workers who feel satisfied with their jobs tend to display voluntary behavior at work that exceeds the formal rules of the organization (Sofiah et al, 2022). Millennial job satisfaction can increase their commitment to their organization (Pradipto & Chairiyati, 2021).…”
Section: Introductionmentioning
confidence: 99%